To see the world in a grain of sand: integrating techniques and phases to reconstruct more complete geological histories - Dröllner, Maximilian (Curtin University, 2022)
This thesis aims to address limitations of sedimentary provenance analysis in sediments with complex grain histories, such as heavy mineral sand deposits. To refine source-to-sink interpretation, the work presents new approaches and tools with a particular focus on intermediate stages of sedimentary systems, namely transient sediment storage and sediment recycling. Ultimately, integration of multiple techniques aids to unravel intermediate processes, associated with the upgrading of heavy mineral sands, and generally improves understanding of sedimentary systems.